Prevention of benign paroxysmal positional vertigo with vitamin D supplementation: A randomized trial. (1st September 2020) - Jeong, Seong-Hae; Kim, Ji-Soo; Kim, Hyo-Jung; Choi, Jeong-Yoon; Koo, Ja-Won; Choi, Kwang-Dong; Park, Ji-Yun; Lee, Seung-Han; Choi, Seo-Young; Oh, Sun-Young; Yang, Tae-Ho; Park, Jae Han; et al.
Abstract : Objective: To assess the effect of vitamin D and calcium supplementation in preventing recurrences of benign paroxysmal positional vertigo (BPPV). Methods: We performed an investigator-initiated, blinded-outcome assessor, parallel, multicenter, randomized controlled trial in 8 hospitals between December 2013 and May 2017. Patients with confirmed BPPV were randomly assigned to the intervention (n = 518) or the observation (n = 532) group after successful treatment with canalith repositioning maneuvers. The primary outcome was the annual recurrence rate (ARR). Patients in the intervention group had taken vitamin D 400 IU and 500 mg of calcium carbonate twice a day for 1 year when serum vitamin D level was lower than 20 ng/mL. Patients in the observation group were assigned to follow-ups without further vitamin D evaluation or supplementation. Results: The intervention group showed a reduction in the ARR (0.83 [95% confidence interval (CI), 0.74–0.92] vs 1.10 [95% CI, 1.00–1.19] recurrences per 1 person-year) with an incidence rate ratio of 0.76 (95% CI, 0.66–0.87, p < 0.001) and an absolute rate ratio of −0.27 (−0.40 to −0.14) from intention-to-treat analysis. The number needed to treat was 3.70 (95% CI, 2.50–7.14). The proportion of patients with recurrence was also lower in the intervention than in the observation group (37.8 vs 46.7%, p = 0.005). Conclusions: Supplementation of vitamin D and calcium may be considered in patients with frequent attacks of BPPV, especially when serum vitamin D is subnormal. Classification of evidence: This study provides Class III evidence that for patients with BPPV, vitamin D and calcium supplementation reduces recurrences of BPPV.